Contesting Marital Presumption of Paternity – Biological Father’s Legal Position. Comparative Overview in Albania and the Western Balkan Countries - Juelda Lamçe; Renata Kau (Studia Iuridica Lublinensia, 2023)
This scientific article is focused on the possibility for the biological father to challenge the marital presumption of paternity. Academic studies show that there is an enlargement of legal actions towards the establishment of biological evidence and that non-marital parents have enforceable legal rights. In the Albanian legislation (and in some others as well), there is a different treatment reserved for children born within and out of wedlock. While the biological father is entitled to contest the paternity of a child born out of wedlock, he is not when it comes to children born within wedlock. Thus, the aim of the research is to critically analyse the Albanian legislation on presumed paternity contestation, focusing on the legal position of the biological father of the child. It takes into consideration relevant doctrine, the jurisprudence of the European Court of Human Rights, and comparative legislation in the Western Balkan countries. The main thesis of this paper is that, when contesting the marital presumption of paternity, a fair balancing of competing rights and interests at stake is not reached if the biological father is excluded from the category of persons entitled to contest the presumed paternity.